IDENTIFIKASI INFEKSI SKABIES DAN FAKTOR RISIKO PERILAKU PERSONAL HYGIENE PADA ANAK PANTI ASUHAN AL-JAM’IYATUL WASHLIYAH PULO BRAYAN MEDAN - Mangatas Silaen (PRIMER (Prima Medical Journal), 2020)
Scabies is a skin disease caused by infestation and sensitization of Sarcoptes scabiei variant hominis on the body. Scabies is a contagious disease. Transmission can occur through close physical contact such as shaking hands, sleep together and sexual relations, and can also through underwear, towels, sheets and beds. This research aims to identify risk factors for the infection of scabies and personal hygiene behaviors of orphans in Panti Asuhan Al-Jam'iyatul Washliyah. This research is a descriptive survey with cross sectional. Samples to be examined in this research are orphans in Panti Asuhan Al-Jam'iyatul Washliyah who fulfilled the inclusion criteria. The results of this research describe the orphans in Panti Asuhan Al-Jam'iyatul Washliyah who suffered by scabies as many as 23 people (57.5%) and who didn’t suffer from scabies as many as 17 people (42.5%). And also known as many as 14 people (35%) fall into favorable category of personal hygiene behavior and 26 people (65%) fall into unfavorable category of personal hygiene behavior.